Peran Governansi Digital dalam Meningkatkan Transparansi Layanan Publik di Kabupaten Badung - Ni Luh Putu Ening Permini; I Kadek Dede Junaedy; Ni Komang Cahyani; I Putu Udi Sastrawan (RISOMA : Jurnal Riset Sosial Humaniora dan Pendidikan, 2026)
This study examines the role of digital governance in improving the transparency of public services in Badung Regency. Transparency is a key pillar in realizing good governance, and in the digital era, digital governance is key to achieving this goal. Using a qualitative research method with a case study approach, this study aims to explore the perceptions, experiences, and challenges faced by stakeholders, including civil servants (ASN) and service users, regarding the implementation of digital governance and its impact on transparency. Data were collected through in-depth interviews, participant observation, and analysis of policy documents and public service reports in Badung Regency. The results are expected to provide a comprehensive overview of the digital governance mechanisms that have been implemented, how these mechanisms facilitate information disclosure, and the non-technical barriers that may arise. These findings are expected to contribute to the development of more effective digital governance policies and practices to promote transparency in public services, not only in Badung Regency but also as a model for other regions in Indonesia.